Micronized sacchachitin promotes satellite cell proliferation through TAK1-JNK-AP-1 signaling pathway predominantly by TLR2 activation - Meng-Huang Wu; Chuang-Yu Lin; Chun-Yin Hou; Ming-Thau Sheu; Hsi Chang (BMC, 2020)
Abstract Background Ganoderma sp., such as Ganoderma tsugae (GT), play an important role in traditional Chinese medicine. Ganoderma sp. contains several constituents, including Sacacchin, which has recently drawn attention because it can not only enhance the repair of muscle damage but also strengthen the muscle enforcement. Although Ganoderma sp. have a therapeutic effect for neuromuscular disorders, the underlying mechanism remains unclear. This study investigated the effect and underlying molecular mechanism of micronized sacchachitin (mSC) on satellite cells (SCs), which are known as the muscle stem cells. Methods The myogenic cells, included SCs (Pax7+) were isolated from tibialis anterior muscles of a healthy rat and were cultured in growth media with different mSC concentrations. For the evaluation of SC proliferation, these cultivated cells were immunostained with Pax7 and bromodeoxyuridine assessed simultaneously. The molecular signal pathway was further investigated by using Western blotting and signal pathway inhibitors. Results Our data revealed that 200 µg/mL mSC had an optimal capability to significantly enhance the SC proliferation. Furthermore, this enhancement of SC proliferation was verified to be involved with activation of TAK1-JNK-AP-1 signaling pathway through TLR2, whose expression on SC surface was confirmed for the first time here. Conclusion Micronized sacchachitin extracted from GT was capable of promoting the proliferation of SC under a correct concentration.